Religions of Japan in Practice - Sawada, Janine Anderson 1953-; Andrews, Allan A.; Aoki, Michiko Y.; Bielefeldt, Carl; Bodiford, William M.; Bodijord, William M.; Cay, Suzanne; Deal, William E.; Dobbins, James C.; Dykstra, Yoshiko K.; Earhart, H. Byron; Ebersole, Gary L.; et al. (Princeton University Press, 2021)
This anthology reflects a range of Japanese religions in their complex, sometimes conflicting, diversity. In the tradition of the Princeton Readings in Religions series, the collection presents documents (legends and miracle tales, hagiographies, ritual prayers and ceremonies, sermons, reform treatises, doctrinal tracts, historical and ethnographic writings), most of which have been translated for the first time here, that serve to illuminate the mosaic of Japanese religions in practice. George Tanabe provides a lucid introduction to the "patterned confusion" of Japan's religious practices. He has ordered the anthology's forty-five readings under the categories of "Ethical Practices," "Ritual Practices," and "Institutional Practices," moving beyond the traditional classifications of chronology, religious traditions (Shinto, Confucianism, Buddhism, etc.), and sects, and illuminating the actual orientation of people who engage in religious practices.
Description based on online resource; title from PDF title page (publisher's Web site, viewed 25. Feb 2021)
Keywords: RELIGION / Shintoism